An Analysis of the Market Share-Profitability Relationship - Szymanski, David M.; Bharadwaj, Sundar G.; Varadarajan, P. Rajan (Journal of Marketing, 1993)
A number of researchers in the marketing, management, and economics disciplines have expressed reservations regarding the validity and generalizability of the reported relationships between market share and profitability. Against this backdrop, the authors performed a meta-analysis on 276 market share-profitability findings from forty-eight studies to address whether market share and profitability are positively related and to examine the factors that moderate the magnitude of that relationship. The authors found that, on average, market share has a positive effect on business profitability. However, the magnitude of the market share-profitability relationship is moderated by model specification errors, sample characteristics, and measurement characteristics. The relationship is moderated the most (and, on average, the relationship could be artifactual) when firm-specific intangible factors are specified in the profit model or the estimate of the market share-profitability relationship is based on an analysis of non-PIMS businesses. The authors discuss the implications of these results for the evaluation and utilization of market share information by managers in reference to strategies that focus on building market share as a means for increasing profits.